Application of Fire-Up Learning Strategy can Improve Learning Learning Results on the Points of Fluid in Class XI MIPA 1 SMA Negeri 2 Pekanbaru - Shahn, Sharmila (UIR Press, 2018)
Strategy is a plan or steps that are carried out systematically, which has a system to facilitate the implementation of an activity in order to achieve the purpose specified. The learning process will be effective when learners participate in it and learners do most of the learning activities. The success of learning is influenced by various factors, one of which is the factor of learning strategy. Selection of learning strategy is very important because learning strategy is a way to deliver lesson materials so that in the process of teaching and learning the teacher is not too dominate the learning activities. The dominant thing is that learners only listen.Learning strategy is a planning that contains about a series of activities designed to achieve learning objectives, so that teachers need to understand well the role and function of the strategy in the implementation of the learning process. Active learning strategy can be used as an alternative learning that can improve the quality of physics learning.Learners use their ability to learn various problems and apply what they have learned. Implementation of appropriate learning strategy is expected to overcome the low learning outcomes of learners by making learners as independent learners and create an atmosphere that makes learners active in learning is a learning strategy FIRE-UP. According to Madden FIRE-UP strategy (Foundation, Intake information, Real meaning, Express your knowledge, Use available resources, Plan of action) can make learners more active because learners are made into independent learners.The stages of the FIRE-UP strategy will encourage learners to prepare for the basic knowledge of learners after studying their own textbooks or lesson materials in order to prepare learners to address the unknown (Foundation), how learners can concentrate on incorporating information acquired (Intake Information), creates the true meaning of the new information it receives through the process of assimilation into its real-world knowledge, reveals what is known and asks unknowns through discussion or re-teaches to its peers (Express your knowledge, Use available resources), as well as planning the activities of learners in presenting their group work (Plan of Action).Based on the results obtained the value of the first cycle, the second cycle and the third cycle in a row (77,94%), (81,76%) dan (85,97%).